2018
DOI: 10.3390/w10050587
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Performance of Lined Permeable Pavement Systems in the Built Environment

Abstract: Abstract:The hydraulic performance of permeable pavement (PP) systems has been well demonstrated when based on full or partial on-site infiltration, while there is only limited research on lined PP systems built to provide detention and volume reduction by evaporation only. In this study, we tested the performance of commercially available PP components when constructed as lined PP systems with un-throttled discharge to explore basic hydraulic function in a real-life-setting. Four types of PP surface products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Støvring et al (2018) reported a median centroid delay of 139.5 min for a PICP stall which employed a similar cross‐section to that herein, was lined with an impermeable membrane, and treated only direct rainfall. As Støvring et al (2018) implemented an impermeable liner to eliminate exfiltration from the PICP stalls, the increased centroid lag observed from the Vermilion permeable pavement may be attributable to the interface of the aggregate subbase with native soils, where added roughness (and some exfiltration) would delay (or eliminate) the conveyance of a portion of flows to the underdrain. However, the centroid lag of nearly 20 h reported in Roseen et al (2012) substantially exceeded the centroid lag reported herein.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Støvring et al (2018) reported a median centroid delay of 139.5 min for a PICP stall which employed a similar cross‐section to that herein, was lined with an impermeable membrane, and treated only direct rainfall. As Støvring et al (2018) implemented an impermeable liner to eliminate exfiltration from the PICP stalls, the increased centroid lag observed from the Vermilion permeable pavement may be attributable to the interface of the aggregate subbase with native soils, where added roughness (and some exfiltration) would delay (or eliminate) the conveyance of a portion of flows to the underdrain. However, the centroid lag of nearly 20 h reported in Roseen et al (2012) substantially exceeded the centroid lag reported herein.…”
Section: Resultsmentioning
confidence: 80%
“…However, methods employed to calculate lag time often vary widely between studies, affecting comparisons of this aspect of permeable pavement effectiveness and inhibiting improvement of hydrologic models of these systems. Examples of calculations and lag times reported in previous studies include: time between onset of rainfall and underdrain discharge (Fassman & Blackbourn, 2010), time between centroids of rainfall and underdrain discharge (Roseen et al, 2012; Støvring et al, 2018), time between peak rainfall intensity and peak discharge (Abbott & Comino‐Mateos, 2003; Braswell, Winston, & Hunt, 2018; Vaillancourt et al, 2019), time between centroids of runoff from an asphalt parking lot and underdrain discharge (Drake et al, 2014), and time between peak runoff from a reference asphalt parking lot to peak discharge from the permeable pavement underdrain (Collins et al, 2008). Thus, while the impact of permeable pavements on lag time has been demonstrated in several studies, the array of methodologies used adds uncertainty to the extent to which runoff is delayed by permeable pavements, particularly since other factors also vary among the experiments noted above.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the hydrological benefits of PPs in the last decades (see Drake et al (2013) for review). However, only a few studies were found to investigate the performance of LPP systems (Pratt et al 1995;Abbott & Comino-Mateos 2003;Støvring et al 2018). Abbott & Comino-Mateos (2003) analyzed 20 rainfall-runoff events collected from an LPP site.…”
Section: Introductionmentioning
confidence: 99%
“…They found the LPP to reduce rainfall peaks significantly; a rainfall with 12 mm/h intensity was found to produce a runoff with a peak of 0.37 mm/h. Similarly, Støvring et al (2018) investigated the hydraulic performance of several LPP plots with different layers and equal surface areas (25 m 2 each). During a period of 12 months, they observed a total of 22 rainfall-runoff events with return periods up to 2 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation